2004
DOI: 10.1007/s00018-004-3417-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection blocks apoptosis in cancer cells

Abstract: Recent pathological findings reveal a higher frequency of human cytomegalovirus (HCMV) in tumor cells from different tumors compared with surrounding tissues. Experimental investigations suggest possible supportive effects of HCMV for tumor development and progression. One HCMV effect on tumor cells is the inhibition of apoptosis, leading to the promotion of tumor cell survival. Decreased sensitivity to treatment-induced tumor cell death is a major reason for failure of anticancer chemotherapy. HCMV infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 98 publications
0
16
0
Order By: Relevance
“…Studies from this laboratory and others have also demonstrated that HCMV infection can cause severe endothelial dysfunction, e.g. dysregulated apoptosis (Kovacs et al, 1996;Reboredo et al, 2004;Shen et al, 2004) and hampered apoptosis in HeLa cells (Zhu et al, 1995), cancer cells (Michaelis et al, 2004) and fibroblasts (Reboredo et al, 2004). We previously reported that p53 is stabilized in the nucleus at the early stage of HCMV infection and becomes sequestrated in the cytoplasm at the later stage of the infection (Kovacs et al, 1996;Wang et al, 2001;Wang et al, 2000).…”
Section: Introductionmentioning
confidence: 91%
“…Studies from this laboratory and others have also demonstrated that HCMV infection can cause severe endothelial dysfunction, e.g. dysregulated apoptosis (Kovacs et al, 1996;Reboredo et al, 2004;Shen et al, 2004) and hampered apoptosis in HeLa cells (Zhu et al, 1995), cancer cells (Michaelis et al, 2004) and fibroblasts (Reboredo et al, 2004). We previously reported that p53 is stabilized in the nucleus at the early stage of HCMV infection and becomes sequestrated in the cytoplasm at the later stage of the infection (Kovacs et al, 1996;Wang et al, 2001;Wang et al, 2000).…”
Section: Introductionmentioning
confidence: 91%
“…52 In addition, HCMV has been reported to induce the antiapoptotic cellular proteins AKT, Bcl-2, and Np73. 53 Clearly, these observations indicate that blocking cellular apoptosis is an essential characteristic of the virus. Therefore, one explanation for the HCMV induction of IL-6-mediated antiapoptosis described in this report is that this pathway may represent a redundant mechanism for the virus to maintain cellular survival of persistently HCMV-infected ECs.…”
Section: Il-6 In Hcmv Secretome Induces Angiogenesis 359mentioning
confidence: 99%
“…It also is a leading viral cause of birth defects (7). HCMV infection triggers a series of cellular responses and modulates normal cellular functions, including initiating signal transduction pathways, alternating cell cycle controls, preventing apoptosis, and allowing escape from the immune system (8,14,19,22,27,45).…”
Section: Human Cytomegalovirus (Hcmv) Infection Directly Initiates a mentioning
confidence: 99%